Kemampuan CEO Narcissism dalam Hubungan Manajemen Laba dan Nilai Perusahan (The Ability of CEO Narcissism in the Relationship between Earnings Management and Firm Value) - Sugianto, Tri Wahyuni Rukmana; Wijaya, Riesanti Edie (STIE Malangkucecwara, 2024)
Top management narcissism is often perceived as a bad thing that has the potential to worsen the condition of the company. This study aims to explain how CEO narcissism affects the relationship between EM and firm value. We used a sample of 152 financial statements of the listed companies on the Indonesia Stock Exchange between 2016 and 2020. We used multiple linear tests to analyze the data. The study describe that EM and CEO narcissism can individually increase firm value. Meanwhile, when narcissism is used as moderation, it weakens firm value. This suggests that EM and CEO narcissism both have great power to improve corporate image with an increase in FV. However, the moderation of CEO narcissism decreases firm value. This study provides a new discourse that CEO narcissism is also a strong signal that investors consider in conducting their economic activities, rather than when it plays a moderating role.